How I learned geography - Shulevitz, Uri, 1935- (Farrar Straus Giroux, 2008)
As he spends hours studying his father's world map, a young boy escapes the hunger and misery of refugee life. Based on the author's childhood in Kazakhstan, where he lived as a Polish refugee during World War II.